Pengembangan e-Modul Integratif untuk Melatih Literasi Numerasi Materi Peluang pada Kurikulum Merdeka - Rosyidah, Novia Mar'atur; Mukmin, Muhammad Islahul (Arithmetic (online), 2024)
The aim of this research is to develop an integrative e-module based on numeracy literacy on probability material in the Kurikulum Merdeka that is valid and practical. The type of research used is research and development (R&D) with the ADDIE development model. The research was conducted at Islamic Senior High School 3 Kediri. Research data was collected from expert validation questionnaires and response questionnaires. The percentage of questionnaire scores obtained by material expert validation was 84%, validation by integration experts was 71.7%, validation by learning experts was 75.2%, and validation by media experts was 98.7%. The teacher response results obtained a score percentage of 96.3%, the student response results in the limited trial were 94.4%, and the student response results in the field trial were 77.4%. The average validation score was 82.4% in the very valid category. The average student and teacher response score was 89.4% in the very practical category. Based on the research and development process, it can be concluded that the integrative e-module product based on numeracy literacy, opportunity material in the Kurikulum Merdeka is very valid and very practical to use.